Cell-free DNA screening in twin pregnancies - Hye Yeon Boo; You Jung Han (Korean Society of Obstetrics and Gynecology, 2024)
Cell-free DNA (cfDNA) screening for fetal aneuploidies is clinically available and exhibits better performance than conventional serum screening tests. However, data on the clinical performance of cfDNA screening in twin pregnancies are limited. In this review, we summarized the clinical performance and evaluated the feasibility of cfDNA screening in twin pregnancies based on recent studies and recommendations. The performance of cfDNA screening for trisomy 21 in twin pregnancies is similar to that in singleton pregnancies. Specifically, cfDNA screening has a higher detection rate and lower false-positive rate compared with conventional serum screening. Consequently, recent international guidelines from several academic communities have recommended that cfDNA screening for aneuploidy in twin pregnancies could be considered. Moreover, twin pregnancies can present with specific conditions, such as different zygosities and vanishing twins; therefore, individualized counseling and management are required. Further clinical studies with more twin pregnancies are required for a more accurate analysis.